Pertanggungjawaban Pidana terhadap Pelaku Perbudakan Anak - Nyoman Ananda Bimastara; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
The participation of children in the labor sector is increasing, as in Indonesia which is a very important aspect in the field of child protection in general. Employment economic aspects of Indonesian society now and in the future remain open to child labor which is often abused so that slavery often occurs. The purpose of this study is to uncover the criminal penalties for perpetrators of child slavery. This type of research is normative legal research with a cases and conceptual approach. Legal sources are primary and secondary legal sources, while data collection techniques are carried out by examining existing library materials which are then analyzed systematically. The results of the study reveal that entrepreneurs/businesses that employ children who violate or limit the work carried out to develop their children's talents and income are punished with imprisonment of 1 to 12 months and/or fined.